The breaking of secrecy: Analysis of the hashtag #MeTooInceste regarding testimonies of sexual incest abuse in childhood. (January 2022) - Idoiaga Mondragon, Nahia; Eiguren Munitis, Amaia; Belasko Txertudi, Maitane
Abstract: Background: Incest remains one of the great taboos of contemporary society. Secrecy is also crucial in this type of sexual abuse against children, and many victims do not disclose their testimony. This situation changed, when in France in mid-January 2021, the #MeTooIncest movement emerged, and thousands of victims began to reveal the abuse they had suffered as children. Objective: To analyze the discourse on Twitter regarding this hashtag to understand how incest abuse has been dealt with through social media debate. In so doing, we expected to identify the main elements that could explain how people have symbolically constructed and engaged with childhood sexual abuse in general and with incest abuse in particular. Participants and setting: In total, 20, 556 tweets with the hashtag #MeTooIncest written in French were selected by streaming API from January 14 to February 15, 2021. Methods: Their content was analyzed by lexical analysis using Iramuteq software (Reinert method). Results: Victims found a space for disclosure in this movement, where they felt believed, protected, and supported. This movement also embraced the victims of celebrity abusers, denouncing them and calling for their exclusion from public life. Likewise, at the societal level, this movement pushed for changes in public policies to protect children and emphasized the importance of breaking the public silence or secrecy about incest abuse. Conclusions: This wave of testimonies represents a turning point as it has broken the law of silence and allowed the victims to exist in the media space without being questioned.